Cinematic Ekphrasis of Lost Films in Fiction: From Representation to Transmediation - Anna Klishevich (Acta Universitatis Sapientiae: Film and Media Studies)
The paper studies cinematic ekphrasis, the representation of film in another medium, and the practice of media transformation. It analyses how lost films are represented and their media characteristics are transmediated in fiction. The article starts with building the connection between ekphrasis and two types of media transformation, media representation and transmediation of media characteristics. It presents an overview of lost films as a subcategory of the film medium drawing on their uncanny characteristics. The argumentation proceeds with the analysis of Jonathan Coe’s novel The House of Sleep (2014), focusing on the ways the cinematic ekphrasis of lost films operates. The paper draws a conclusion on the uncanny effect of cinematic ekphrasis of lost films and the interrelatedness of media representation and transmediation of media characteristics in its practices.